An Analyze Stability of Traditional Boat in Riau Island - Sapto Wiratno Satoto (LPPM ITK, 2021)
Traditional boat are quite important means of transportation in the Riau Islands because of their natural contours consisting of islands. Boat is the main transportation and also lest costs because it only uses simple technology and simple maintenance. This paper is aims to investigate the traditional boat of Riau's curiosity. It is used to find the things that must be prepared with possible dangers arising from the stability of the boat. This research was conducted by collecting data on the main dimension of the traditional boats used in the Riau Islands. From the main dimensions, measurements are made of the shape of the vessel using digital equipment (infrared) combined with simple equipment to obtain maximum results. From the measurement results, then the simulation is carried out using software with several criteria to get the desired results. From the research results, it is found that the boat still has adequate stability on the: lightweight condition, lightweight with 1 person on board and engine, lightweight with one person onboard with engine and even load. In the future, research will continue to simulate loading when the boat will be used to transport people, luggage with variations in wave angle and boat direction.